Pesticide Labeling: Unique Product Labeling - Frederick M. Fishel (EDIS)
This document explains unique approaches taken by the EPA for how pesticide label information is conveyed for pesticide products that are contained in non-traditional packages. Several examples are provided. This document is PI-110, one of a series of the Agronomy Department, UF/IFAS Extension. Original publication date March 2006.